Feasting in society: A cace study in Aceh Besar district, Aceh province, Indonesia - Izwani Sahardin; Fatan Hamamah Yahaya (Proceedings of AICS - Social Sciences, 2013)
Feasting is often associated with the elements of culture, life cycle, income level and gratitude of society. Whilst in the Nanggore Aceh Darussalam, feasting is always synonym with the great days of the Islamic religion. Food preparation during the festivities form a unique social identity to the Achenese. This paper explains the social structural elements in the process of food preparation, types of food serve during each ceremony in the Islamic calender and the social status of the society. The main objective of the study is to categorize the types of food prepared for the society in association to the human life cycle, i.e. custom that takes place during one’s birth, circumcision, engagement, marriage and death. The study is ethnographic in nature and uses in-depth interview and participant observation methods in data collection. 28 informants were selected based on snowball method and data were analysed using descriptive analysis. Findings showed that feasting in the Aceh Besar society has a structure in accordance with the type of ceremony or ritual performed. In particular the categorization of feast food refers to meal, one dish meal, snacks and fruits. Feast food like Bu Kulah, Bu Leukat Pisang Peungat and Sie Reuboh have formed varity, taste, nutritional value and cultural identity of Aceh Besar society.Keywords: feasting, culture, identity, ceremony, Aceh Besar society